Arsenic accumulation in crops in relation to their water requirement - Sultana, Sharmin; Rashid, Md Harunur; Huq, SM Imamul (Bangladesh Journal of Scientific Research, 2016)
A pot experiment was conducted to study the transfer of arsenic (As) from soil to plant and to know the relation between arsenic accumulation and water requirement. The plants BR-29, BR-28, Red amaranthus (Lalshak) and Ipomoea aquatica (Kalmishak) were selected for this experiment. The control pots were irrigated with tap water and the treatment pots were irrigated with arsenic contaminated water. Different plant parts such as roots, straw, leaf and seeds of rice and roots, shoots, leaves of Lalshak and Kalmishak were analyzed. It was found that arsenic concentration was higher in the plants that were irrigated with arsenic contaminated water. Maximum arsenic concentration was found in roots and the minimum in leaves. The arsenic accumulation depended on the type of crops and varieties. The present study revealed that arsenic accumulation is higher in those plants that have higher water requirement. BR-29 needs more water than BR-28 and as a result BR-29 accumulated more arsenic than BR-28. Similarly Ipomoea aquatica accumulated more arsenic than Red amaranthus. From the experiment it was concluded that if irrigation is continued with arsenic contaminated water for a long time, arsenic may enter into the food chain beyond permissible limit and may cause human health risk. Bangladesh J. Sci. Res. 28(2): 171-180, Dec-2015